The Effect of Sulphydryl and Enzyme Inhibitors on Platelet Aggregation in Vitro - Harrison, M. J. G; Emmons, P. R; Mitchell, J. R. A (Thrombosis and Haemostasis, 1966)
The glycolytic enzyme poisons potassium cyanide, sodium fluoride, and monofluoroacetate do not inhibit platelet clumping. The sulphydryl inhibitors, n-ethyl maleimide and p-hydroxymercuribenzoate, inhibit platelet aggregation produced by ADP, ATP, nor-adrenaline, 5HT, thrombin and connective tissue extract. This inhibitory activity is counteracted by 1-cysteine. These results suggest that platelet thiol groups are involved in the platelet adhesion occurring during aggregation.